The dynamics and dimensions of intra-party conflict: Introduction to the special issue. (September 2019) - Gherghina, Sergiu; Close, Caroline; Kopecký, Petr
Existing research on intra-party unity and conflict has mostly focused on (dis)unity within the legislative branch of the party at the national level, while neglecting conflict between the different faces or at different levels of the party. Intra-party unity and conflict have also been routinely defined and operationalized through ideological homogeneity or distance, although intra-party conflicts are multidimensional and dynamic phenomena. The articles included in this special issue seek to address these shortcomings in the literature. Their contributions are threefold: (1) they theorize intra-party conflict as a dynamic and multifaceted concept; (2) they explore conflicts across and between several party faces, and among different intra-party actors; (3) they investigate the determinants and management of conflict at several party levels.